A study on ion – Exchange properties of some terpolymer resins. (2022) - Sabitha, B.; Sanjeeva Rao, B.; Chandra Mouli, B.; Sharma, Renu
Abstract: Ion – exchange resins play important role in the removal various types of pollutants and purification ofwater and oil recovery industries. In the present work, the authors report on ion – exchange properties of ter-polymer resins based on 2–4 di-hydroxy phenyl alkyl ketone / furfural / formaldehyde (DHPPE-FF- MM). Ion – exchange behavior of DHPPE-FF-MM resin is examined for selectivity of Fe2+, Cu3+, Ni2+, Co 2 +, Zn2+, Cd2+ and Pb2+ ions in the presence of various electrolytes of different concentrations and PH value. The batch equilibrium method is used to study selectivity of metal ion uptake involving different metal ions and various electrolytes having different ionicities. The ter-polymer resin has shown highest selectivity for the Cu 2+ metal ion than the remaining ions. Further, comparison in rates of metal ion uptake by the polymer resin in the presence of various electrolytes of different concentrations and PH values are also investigated. Distribution of metal ions in an electrolyte with different concentration and PH are also presented.